On Gevrais classes of certain self-adjoint differential operators with degeneration - Izvekov, I. G.; Martynenko, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Classical spaces of ultra-diffcrentiable funetions on [-1,1] are compared with the Gevrais classes of а self-adjoint differentiable operator whose eigenfunetions an the orthogonal Jacobi polynomials.